Analysis Of Creative Employment Of Texts In Laz Ekwueme’s Vocal Works - Mary Taiwo Omotosho (Accelerando: BJMD)
In furtherance of scholarly contributions to documentation of the works of notable Nigerian art music composers, this paper aims to bring to limelight Laz Ekwueme’s creative employment of texts in his vocal works. He was the only composer among his contemporaries without any musical influence from his parents, and with no financial comfort. Due to the composer’s proficient and dynamic application of texts in his works, the paper is set to trace the source of Ekwueme’s passion for music in connection to his creative usage of texts, and analyse his compositions accordingly. This study relies on interviews held with the composer, score reading of his music compositions, and relevant literature. The paper is anchored on the theory of creative ethnomusicology, pioneered by Akin Euba, in describing Ekwueme’s musical artistry in text-setting of his compositions. Various thematic vocal works comprising thirty (30) sacred and secular music were analysed, some of which include carols, fanfare, anthem, spirituals, folk songs, glee, mass, and introits. The analysis reveals poetic creativity, rhyme patterns, symmetrical lines/alignments, cultural permutations, lyric syllabification, re-appropriation of texts in arrangements of existing works, text-juggling, careful text-setting to music, new formation and application of existing nonsensical syllables for emphasis, humorous textual employment, and general aesthetics. In conclusion, Ekwueme’s texts, sourced as influenced by his environments, are anchored and evidenced in the creative application of information gathered from his music research. His method of textual employment will enhance the compositional skills of upcoming art music composers.